Challenges in Teaching Good Manners and Right Conduct at The Intermediate Level: Educators’ Perspective - Gemcer Selda; Jenny Joy S Inocencio; Maria Christina B Magracia (Advanced Qualitative Research, 2025)
This study explored the challenges faced by Grade 4 public school educators in teaching Good Manners and Right Conduct (GMRC) and the strategies they use to address them. Using a qualitative phenomenological approach, eight (8) teachers from the Bongabong North District with at least two years of teaching experience were interviewed. Findings revealed several challenges, including cultural diversity, lack of student discipline, social media influence, behavioral issues, limited teaching materials, and insufficient training. Despite these difficulties, teachers applied strategies such as storytelling, role modeling, and experiential learning to promote moral values and discipline among students. The study also emphasized the importance of a well-managed classroom, where student cooperation and engagement play a key role in the success of GMRC instruction. Furthermore, teachers stressed that parental and community involvement is vital in reinforcing values education beyond the school setting. In addition, this research contributes to the application of qualitative methodology in education by demonstrating how phenomenological inquiry can capture the lived experiences of teachers and provide insights into value-laden instruction.